EVALUASI REAKSI OBAT TIDAK DIKEHENDAKI AMLODIPINE DAN CAPTOPRIL PADA PASIEN HIPERTENSI DI PUSKESMAS WINDUAJI PAGUYANGAN TAHUN 2024 - Luthfi Hidayat; Puput Pamulasih; Teguh Hary Kartono (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2025)
Hypertension is a condition in which a patient's blood pressure is higher than normal, namely 140/90 mmHg. Seeing the reality that antihypertensive treatment causes several unwanted drug reactions and patients who are treated with complaints and symptoms of hypertension will get antihypertensive prescriptions such as amlodipine or captopril. The purpose of this study was to determine the type of adverse drug reactions to amlodipine or captopril in hypertensive patients and the percentage of patients who experienced adverse drug reactions. This study uses an observational method that is descriptive in nature. Data collection was carried out prospectively, namely direct interviews. The population of hypertensive patients from April to September 2023 is 1,011 patients with an average sample in this study of 168 patients. The sampling technique in this study uses purported sampling by examining subjects against inclusion and exclusion criteria. The inclusion criteria in this study were hypertensive patients who received amlodipine or captopril therapy and patients who were willing to become respondents while the exclusion criteria in this study were hypertensive patients who were not willing to become respondents and hypertensive patients who did not use amlodipine or captopril. The total sample included in the inclusion criteria was 108 patients. The results showed that there were unwanted drug reactions in patients who received amlodipine therapy in 12 patients (11.1%) and the types of unwanted drug reactions in hypertensive patients with amlodipine therapy were 1% edema, 2.9% gastrointestinal , gastrointestinal and back pain as much as 2.9%, back pain as much as 2.9%, palpitation as much as 1%, frequent urination as much as 1% and no unwanted drug reactions as much as 88.5%. In hypertensive patients who received captoril therapy, there were no unwanted drug reactions in 4 patients with a percentage of 100%.